The Effect of Sensory-Friendly Learning Environments and Teacher Support on Students’ Learning Comfort in Inclusive Classrooms in Indonesia - Anizar Anizar; Istiarsyah Istiarsyah; Riki Taufiki; Retno Triswandari; Amel Yani (Jurnal Pendidikan West Science, 2026)
This study examines the effect of a sensory-friendly learning environment and teacher support on students’ comfort in inclusive classrooms in Indonesia. Inclusive education requires classroom conditions that accommodate diverse student needs, particularly in relation to sensory processing differences and interpersonal support systems. A quantitative approach was employed using a survey method involving 150 students selected through non-probability sampling. Data were collected using a Likert scale questionnaire and analyzed using SPSS version 25 through multiple linear regression analysis. The results indicate that both a sensory-friendly learning environment and teacher support have a positive and significant effect on student comfort. Teacher support is found to have a stronger influence compared to environmental factors. The model explains 61% of the variance in student comfort. These findings emphasize the importance of integrating environmental adjustments with effective teacher support to enhance learning comfort in inclusive classrooms in Indonesia.